(untitled) (Research, Society and Development, 2023)
Individuals diagnosed with Autistic Spectrum Disorder (ASD) may have a delay in the development of verbal repertoire, such as echoic responses. It is common in speech therapist practice to use multisensory cues to establish and refine echoic repertoire. Due to the context of COVID-19 Pandemic in 2021, the Federal Council of Speech Therapy (CFFa) determined the use of surgical mask or N95 while delivering patient care, and the use of transparent masks was discouraged. In this context, in order to show the patient a visual vocal model that he or she needs to reproduce, the CFFa advised speech therapists to use illustrative video recordings of vocal models. Since there is a deficit of empirical knowledge related to this recommendation, the current study sought to verify whether visual multisensory cues presented through videos would be effective in speech accuracy of echoic responses in individuals with ASD. Three children diagnosed with ASD and Childhood Apraxia of Speech participated. After obtaining control data with each participant (in a single subject, multiple probe experimental design), the treatment was implemented with the introduction of the vocal video modelling. The data reported show thar only one participant was able to reach the programmed performance accuracy. This study did not confirm the effectiveness of the procedure and point out the need for additional empirical research to improve the use of video modelling techniques to teach echoic behavior with this population. A starting point for studies of procedural variables in teaching echoic repertoire via videomodelling is provided here.